Celowość zastosowania koncepcji opcji realnych w działalności przedsiębiorczej - Bratnicki, Mariusz; Austen, Agata (Functionality of Using Real Options Concept in Enterprising Activity, 2024)
Creating successful ventures requires both achieving strategic flexibility and making change in perceiving uncertainty. Consequently with the venture growth it is followed by the process of learning that enables individuals to recognize new opportunities which couldn't have been foreseen before. Yet, intelligent responding to the changes of environment causes a number of difficulties. These barriers in achieving effective entrepreneurial process can be mitigated by using real options reasoning, which is the key concept for further analysis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 230-237